The search of new knowledge in the firm’s innovation process: a literature review - Donato, Alessia (Journal of Mathematical Economics and Finance; Vol 7 No 2 (2021): JMEF, Volume VII, Issue 2(13), Winter 2021, 2021)
We propose an examination of the current literature on innovation, taking into account, specifically, the concept of knowledge diversity and knowledge recombi- nation. We analyze bibliometric data using the software VOSviewer and we derive indications on the principle analyzed research fields, where they come from and in what directions they are going.